PUB4, a CERK1-Interacting Ubiquitin Ligase, Positively Regulates MAMP-Triggered Immunity in Arabidopsis. (1st August 2019) - Desaki, Yoshitake; Takahashi, Shohei; Sato, Kenta; Maeda, Kanako; Matsui, Saki; Yoshimi, Ikuya; Miura, Takaki; Jumonji, Jun-Ichi; Takeda, Jun; Yashima, Kohei; Kohari, Masaki; Suenaga, Takayoshi; et al.
Abstract: Lysin motif (LysM) receptor-like kinase CERK1 is a co-receptor essential for plant immune responses against carbohydrate microbe-associated molecular patterns (MAMPs). Concerning the immediate downstream signaling components of CERK1, receptor-like cytoplasmic kinases such as PBL27 and other RLCK VII members have been reported to regulate immune responses positively. In this study, we report that a novel CERK1-interacting E3 ubiquitin ligase, PUB4, is also involved in the regulation of MAMP-triggered immune responses. Knockout of PUB4 resulted in the alteration of chitin-induced defense responses, indicating that PUB4 positively regulates reactive oxygen species generation and callose deposition but negatively regulates MAPK activation and defense gene expression. On the other hand, detailed analyses of a double knockout mutant of pub4 and sid2, a mutant of salicylic acid (SA) synthesis pathway, showed that the contradictory phenotype of the pub4 mutant was actually caused by abnormal accumulation of SA in this mutant and that PUB4 is a positive regulator of immune responses. The present and recent findings on the role of PUB4 indicate that PUB4 is a unique E3 ubiquitin ligase involved in the regulation of both plant immunity and growth/development.